Leveraging Blockchain for Transparency: A Study on Organ Supply Chains and Transplant Processes - Rashmi Ranjan Panigrahi; Subhodeep Mukherjee; Zakir Hossen Shaikh; Naji Mansour Nomran (Logistics, 2025)
Background: Organ transplants require proper monitoring and tracking. This research examines the adoption of blockchain in the organ supply chain to bring transparency and help patients avoid the fraud that may be faced in the organ transplant process. This study aims to develop a framework and measure for creating transparency in the organ supply chain. A rigorous literature review identified eight constructs for blockchain adoption in organ supply chains and proposed hypotheses. Methods: Using a structured questionnaire, 286 valid responses were collected from the hospitals. Structural equation modelling was used to test and validate the model. Results: The study’s findings indicate that social influence, trust, facilitating conditions, government support, performance expectancy, data security and privacy, and technology affinity positively impact blockchain adoption in organ transplants. The hypothesis that was rejected was related to effort expectancy and technology readiness. Most respondents agreed that blockchain technology is necessary for a tracking and tracing system in the organ supply chain. Conclusions: This research will support transparency in the organ supply chain, eliminate intermediaries from organ transplants, and ensure organ quality, ultimately benefiting the organ donor and receiver.